Design and rationale of dabigatran's stroke prevention in real life in Turkey (D-SPIRIT) - Uğur Önsel Türk; Emin Alioğlu; Eşref Tunçer; Mehmet Emre Özpelit; Nihat Pekel; İstemihan Tengiz; Nurullah Çetin; Onur Dalgıç; Caner Topaloğlu; Nazile Bilgin; Cihan Altın; Tolga Özdemirkıran; et al. (KARE Publishing, 2016)
Objective: The D-SPIRIT registry is designed to investigate the safety and efficacy of dabigatran etexilate in patients with nonvalvular atrial fibrillation (NVAF) and to collect data on outcomes in clinical practice. Methods: The D-SPIRIT is a national, prospective, observational, post-marketing registry involving patients with NVAF who have been taking dabigatran etexilate therapy for stroke prevention for a minimum of 6 months prior to enrollment. The registry will collect and analyze data from routine care, enrolling up to 600 patients in 9 centers. Patients will be followed up for 2 years to evaluate effectiveness and safety. A sample size of 600 subjects is proposed based on the following assumptions; Two-sided significance level of 0.05 (1-sided significance level of 0.025), ischemic stroke incidence rate of 0.768%-1.111%, hemorrhagic stroke incidence rate of 0.109%-0.130%, transient ischemic attack incidence rate of 0.722%-0.623%, therapy discontinuation incidence rate of 40% at day 730, and duration of enrollment period of 12 months with non-uniformed enrollment rate. Ethics approval was given by Dokuz Eylül University Ethics Committee of Clinical Research (2014/54) and approved by the Turkish Ministry of Health. Conclusion: Potential results of D-SPIRIT registry will add data from clinical practice to those from the RE-LY trial to expand knowledge of dabigatran etexilate treatment in patients with NVAF.